The Effect of Growth Differentiation Factor 8 (Myostatin) on Bone Marrow–Derived Stem Cell–Coated Bioactive Sutures in a Rabbit Tendon Repair Model. (March 2020) - Muraoka, Kunihide; Le, Wei; Behn, Anthony W.; Yao, Jeffrey
Background: We have reported that bioactive sutures coated with bone marrow–derived mesenchymal stem cells (BMSCs) enhance tendon repair strength in an in vivo rat model. We have additionally shown that growth differentiation factor 8 (GDF-8, also known as myostatin) simulates tenogenesis in BMSCs in vitro. The purpose of this study was to determine the possibility of BMSC-coated bioactive sutures treated with GDF-8 to increase tendon repair strength in an in vivo rabbit tendon repair model.Methods: Rabbit BMSCs were grown and seeded on to 4-0 Ethibond sutures and treated with GDF-8. New Zealand white rabbits' bilateral Achilles tendons were transected and randomized to experimental (BMSC-coated bioactive sutures treated with GDF-8) or plain suture repaired control groups. Tendons were harvested at 4 and 7 days after the surgery and subjected to tensile mechanical testing and quantitative polymerase chain reaction.Results: There were distinguishing differences of collagen and matrix metalloproteinase RNA level between the control and experimental groups in the early repair periods (day 4 and day 7). However, there were no significant differences between the experimental and control groups in force to 1-mm or 2-mm gap formation or stiffness at 4 or 7 days following surgery.Conclusions: BMSC-coated bioactive sutures with GDF-8 do not appear to affect in vivo rabbit tendon healing within the first week following repair despite an increased presence of quantifiable RNA level of collagen. GDF-8's treatment efficacy of the early tendon repair remains to be defined.